From Natural Language Requirements to Passive Test Cases Using Guarded Assertions - Daniel, Flemstrom; Eduard, Enoiu; Wasif, Azal; Daniel, Sundmark; Thomas, Gustafsson; Avenir, Kobetski (2018 IEEE International Conference on Software Quality, Reliability and Security (QRS), 2018)
In large-scale embedded system development, requirements are often expressed in natural language. Translating these requirements to executable test cases, while keeping the test cases and requirements aligned, is a challenging task. While such a transformation typically requires extensive domain knowledge, we show that a systematic process in combination with passive testing would facilitate the translation as well as linking the requirements to tests. Passive testing approaches observe the behavior of the system and test their correctness without interfering with the normal behavior. We use a specific approach to passive testing: guarded assertions (G/A). This paper presents a method for transforming system requirements expressed in natural language into G/As. We further present a proof of concept evaluation, performed at Bombardier Transportation Sweden AB, in which we show how the process would be used, together with practical advice of the reasoning behind the translation steps.